1985
DOI: 10.1111/j.1474-919x.1985.tb05034.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection of nest sites by a hole‐nesting duck, the Goldeneye Bucephala clangula

Abstract: Nest site preferences were examined for a population of Goldeneye Ducks breeding in nest boxes in Värmland, central Sweden. Some nest boxes were occupied more often than others even if females returning to the same nest box were excluded from the analysis. Nest boxes located higher up trees were occupied more often than those close to the ground and some spatial ‘cluster groups’ of boxes were occupied more often than others. Otherwise nest site prefernces were not related to any measured physical attributes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Goldeneyes Bucephala clangula prospect for nest sites (Eadie & Gauthier 1985, Zicus & Hennes 1989. and birds which nested in sites used previously, and especially those sites which were previously successful, had high nesting success (Dow & Fredga 1985). Cavity-nesting species tend to be nest site limited at some level: therefore, searching for successful sites the year before could save valuable time.…”
Section: Discussionmentioning
confidence: 99%
“…Goldeneyes Bucephala clangula prospect for nest sites (Eadie & Gauthier 1985, Zicus & Hennes 1989. and birds which nested in sites used previously, and especially those sites which were previously successful, had high nesting success (Dow & Fredga 1985). Cavity-nesting species tend to be nest site limited at some level: therefore, searching for successful sites the year before could save valuable time.…”
Section: Discussionmentioning
confidence: 99%
“…Common goldeneye females usually nest for several successive years in the same nest site if the previous nesting attempt has been successful but change the nest site after a failed attempt (Dow andFredga 1983, 1985;H. Pöysä, P. Runko, and A. Paasivaara, unpublished data).…”
Section: Empirical Contextmentioning
confidence: 96%
“…Data for R (i.e., predation vulnerability of nest sites) are difficult to gather, even in a long-term study, because a given nest site usually is not occupied every year and, in particular, because a given nest site usually remains unoccupied for one or more years after a depredated nesting attempt (Dow and Fredga 1983;H. Pöysä, unpublished data).…”
Section: Empirical Contextmentioning
confidence: 98%
“…Pöysä (2006) found that successful nest sites were prospected more frequently by goldeneye females than unsuccessful nest sites, a pattern also found by Zicus and Hennes (1989). Previous studies have shown that nesting goldeneye females favour nests that have been successful in the previous breeding season (Eriksson 1979, Dow and Fredga 1983, 1985), resulting in long periods of years in which there are consecutive nesting attempts in a given nest site (Dow and Fredga 1985; see also Paasivaara and Pöysä 2008). Our present findings add to this pattern by showing that frequently occupied (and successful) nest sites are favoured by parasites year after year, while other, less frequently occupied nest sites do not attract parasites.…”
Section: Discussionmentioning
confidence: 65%